2017
DOI: 10.18632/oncotarget.14562
|View full text |Cite
|
Sign up to set email alerts
|

PDE5 inhibitors enhance the lethality of [pemetrexed + sorafenib]

Abstract: The combination of pemetrexed and sorafenib has significant clinical activity against a wide variety of tumor types in patients and the present studies were performed to determine whether sildenafil enhances the killing potential of [pemetrexed + sorafenib]. In multiple genetically diverse lung cancer cell lines, sildenafil enhanced the lethality of [pemetrexed + sorafenib]. The three-drug combination reduced the activities of AKT, mTOR and STAT transcription factors; increased the activities of eIF2α and ULK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Over the next 6-18 months the NSCLC tumors evolve so that they become resistant to the kinase inhibitory drugs. It is known from in vitro studies that ERBB1 inhibitors reduce the expression of immunotherapy biomarkers such as PD-L1 in NSCLC cells and tumors from kinase inhibitor resistant patients express low levels of PD-L1 and PD-L2 [ 43 , 44 , 45 46 ]. In NSCLC, low levels of immunotherapy biomarkers correlate with a poor anti-tumor response to anti-PD-1 and anti-CTLA4 inhibitory antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Over the next 6-18 months the NSCLC tumors evolve so that they become resistant to the kinase inhibitory drugs. It is known from in vitro studies that ERBB1 inhibitors reduce the expression of immunotherapy biomarkers such as PD-L1 in NSCLC cells and tumors from kinase inhibitor resistant patients express low levels of PD-L1 and PD-L2 [ 43 , 44 , 45 46 ]. In NSCLC, low levels of immunotherapy biomarkers correlate with a poor anti-tumor response to anti-PD-1 and anti-CTLA4 inhibitory antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…(50) The antitumor effect of sorafenib and pemetrexed combination was additionally enhanced by PDE5 inhibitors in NSCLC cells. (51) Varinostat, when combined with gefitinib, strongly inhibited the growth of mutant KRAS lung cancer cells and hepatocarcinoma, but the combination of sorafenib and varinostat did not show such an effect. (52) In conclusion, the present study showed that sorafenib in combination with betulinic acid enhanced the inhibitory effect on NSCLC cells.…”
Section: Discussionmentioning
confidence: 98%
“…Sorafenib combined with gemcitabine or pemetrexed generated a synergistic effect against the A549 cell line . The antitumor effect of sorafenib and pemetrexed combination was additionally enhanced by PDE5 inhibitors in NSCLC cells . Varinostat, when combined with gefitinib, strongly inhibited the growth of mutant KRAS lung cancer cells and hepatocarcinoma, but the combination of sorafenib and varinostat did not show such an effect …”
Section: Discussionmentioning
confidence: 99%
“…[ 41 ] showed the synthetic lethality of the combination of sildenafil, vardenafil or tadalafil with pemetrexed in non-small cell lung cancer (NSCLC) cell lines and in vivo of the combination of sildenafil (5 mg/kg) and pemetrexed. The work has also been extended to show that the combination of sildenafil, pemetrexed and sorafenib enhances the in vivo anti-tumour effects of the pemetrexed + sorafenib combination in a H460 NSCLC model [ 42 ], the combination of celecoxib, sildenafil and sorafenib in a panel of ovarian cancer cells lines [ 43 ] and pemetrexed, sildenafil and sodium valproate in NSCLC and ovarian cell lines [ 44 ]. Domvri et al .…”
Section: Pre-clinical Evidence In Cancer— In Vitro mentioning
confidence: 99%